Exploring in vitro the antiglycant effect, digestive enzyme inhibitor and anti-inflammatory of phenolic extracts from agro-industrial residue : Explorando in vitro o efeito antiglicante, inibidor de enzimas digestivas e anti-inflamatório de extratos fenólicos de resíduos agroindustriais - Fernandes, Annayara Celestina Ferreira, 1989- (2020)
Orientador: Gabriela Alves Macedo